Modifying aluminum phthalocyanine with quantum dots to promote cellular uptake and enhance the efficacy of anticancer photodynamic therapy - Lei, Li; Dai, Bin; Han, Ting; Zhou, Cheng; Gong, Zhao; Zhang, Ping (Frontiers in Materials, 2022)
Photodynamic therapy (PDT) is regarded as an alternative anti-tumor therapy which involves the administration of photosensitizers (PSs) and irradiation with specific light. However, conventional PDT therapy has been limited to the efficiency of PS delivery. A nanocarrier system could provide an effective platform for PS delivery and improve the efficiency of antitumor PDT. In this article, we prepared a complex consisting of aluminum phthalocyanine (AlPcS) and CdSe/CdZnS core-shell structure QDs and investigated the interaction between the complex and tumor cells. A more significant internalization of the conjugation was observed compared to free AlPcS via confocal fluorescence imaging. The tumor cells exhibited an obvious apoptotic trend after QD–AlPcS-mediated PDT.